1956
DOI: 10.1021/ja01604a002
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline Zeolites. II. Crystal Structure of Synthetic Zeolite, Type A

Abstract: The new synthetic zeolite. Type A, is cubic, a" -12.32 A., and X-ray data are consistent with space group 01-Pm.'lni.The unit cell composition is Mei2/" ](A102)i2(Si02)i2]-fVH20 where Me is an exchangeable cation of charge n, and N varies from 20 to 30, The unit cell dimension varies slightly with the cation present. The aluminosilicate framework consists of 24(Si,Al)A), tetrahedra which are joined to form 8-membered oxygen rings in the faces and distorted 6-membeved rings on the 3-fold axes. A large cavity 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
123
0
4

Year Published

1964
1964
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 347 publications
(133 citation statements)
references
References 3 publications
(3 reference statements)
6
123
0
4
Order By: Relevance
“…By March 1954 they achieved their final structure for the A zeolite, verifying it shortly thereafter with single crystal x-ray data on a 30 micron A crystal that Breck and Nancy A. Acara had recently grown [17]. By mid 1954, they also completed the structures of X and faujasite [18], with help from single crystal xray data on faujasite.…”
Section: Crystal Structurementioning
confidence: 82%
“…By March 1954 they achieved their final structure for the A zeolite, verifying it shortly thereafter with single crystal x-ray data on a 30 micron A crystal that Breck and Nancy A. Acara had recently grown [17]. By mid 1954, they also completed the structures of X and faujasite [18], with help from single crystal xray data on faujasite.…”
Section: Crystal Structurementioning
confidence: 82%
“…X-ray powder diffraction and transmission electron diffraction analyses showed that different sodium aluminosilicate solids phases formed from supersaturated nitrate/nitrite-rich sodium aluminate solutions with time during the course of crystallization and followed the sequence: Crystalline phase identification, subsequent to complete transformation of the X-ray indifferent amorphous phase, was performed using established, standard diffraction lines for zeolite, sodalite and cancrinite [1][2][3][4][5][6][7][8] Table 2. Cancrinite (Na 8 Al 6 Si 6 O 24 (NO 3 ) 2 .4H 2 O) Occasionally, particles of about 50 mm wide and 500 nm long were present.…”
Section: Crystallographic Characteristics Of Solid Phasesmentioning
confidence: 99%
“…A high Si/Al ratio gives to the zeolites a high thermal stability [6,7]. The first zeolite was prepared in 1950s under hydrothermal conditions in basic aqueous media and using inorganic cations as charge-balancing species [8][9][10]. Since then, many approaches have been made which have enabled the discovery a large number of new zeolite framework types.…”
Section: Introductionmentioning
confidence: 99%